Sunlight mediated enhanced removal of metoprolol using graphitic carbon nitride (g-C3N4) - Khew, Chung Wei; Leong, Kah Hon; Sim, Lanching; Azrina, Abd Aziz; Dai, Chaomeng; Oh, Wen Da; Shaliza, Ibrahim (Association of American Publishers, 2023)
Graphitic carbon nitride (g-C3N4) is a photocatalyst that has recently been given a lot of attention due to its effectiveness in wastewater and environmental treatment, solar energy utilization, biomedical applications, etc. In this study, g-C3N4 was synthesized and characterized to carry out the degradation of metoprolol tartrate salt (MET), which is classified as an emerging contaminant. MET is one of the most commonly used pharmaceuticals to treat patients with cardiovascular diseases and disorders, a common disease in Malaysia. Recent discoveries of MET in surface waters and drinking water raise awareness and concerns. g-C3N4 was synthesized using solid urea by placing it in a muffle furnace of 550°C for 3 hours. The photocatalytic activities of g-C3N4 were investigated by photodegradation of MET, g-C3N4 of different dosages were added into MET-containing solution, and a dark reaction was carried out for 24 hours for complete adsorption equilibrium. Various physical and chemical analyses were conducted to elucidate the properties of g-C3N4, such as FESEM, FTIR and UV-Vis. The absorbance and reflectance graphs of g-C3N4 show that there will be higher absorption in the visible light spectra. The results show that the optimum dosage to treat 10 ppm of MET is by using 0.3 g of g-C3N4. Under sunlight irradiation of 4 hours, the degradation of MET achieved 54.6% of removal. Hence, it proves that g-C3N4 nanosheet can be applied to remove complex pollutants such as MET under sunlight irradiation. This path is an alternative removal method for MET in a sustainable approach.